Yakut (saha) masalları üzerine bir dil incelemesi (giriş, inceleme, metinler, dizin) - Sağlam, Mehtap Solak (Ege Üniversitesi, 2012)
Sakha Turkish has a crucial place in Turkish Language despite the fact that it is spoken in quite a remote geography and by a small number of people. Many phonological characteristics show us that Sakha Turkish may have existed at the same time as Köktürkçe. Sakha Turkish and Chuvash Turkish are the first dialects of Turkish language that have separated. In this study, I have studied 40 tales written in Sakha Turkish and determined phonetic and formal fetures.The first part of the study is the introduction which is consisted of two sub- parts. In the first sub-part, the place of Sakha Turkish among the Turkish dialects, the political history, the geography, the religion, and the culture of the Sakhas have been studied. In the second sub- part, on the other hand, tales in general and tales in Turkish world have been studied.The most important part of current study is the second one which gives the results of my research. Here, the linguistic features of the tales I have chosen have been examined in detail. This part is consisted of three sub-parts the first of which is phonology in which I have examined the phonological features in the tales. The second sub-part is morphology in which I have studied the morphological features of the tales. In the third sub-part, syntax, I have studies sentence structures and types as wells as word groups.The third part of the study consists of the texts. The texts, here, are given with transcription and in Turkey Turkish besides their originals.The fourth part consists of an index and a glossary. All the words from the tales have been listed together with their meanings. In addition, the places of the words in the tales have been indicated.At the very end, comes the conclusion part in which the content and results of the study have been given. Saha Türkçesi, oldukça uzak bir coğrafyada, az sayıda insan tarafından konuşulmasına rağmen, ses denklikleri ve diğer özellikleri açısından Türk dilinde önemli bir yere sahiptir. Birçok ses özelliği bize Saha Türkçesinin, Köktürkçe ile ...